2017
DOI: 10.1037/npe0000067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative conditioning of established brands: Implicit measures reveal other effects than explicit measures.

Abstract: Evaluative conditioning (EC) effects on established liked and disliked brands were measured via self report, startle reflex modulation (SRM), heart rate (HR), skin conductance (SC), and the Implicit Association Test (IAT). Baseline measures were compared with measures taken after 1, 6, and 16 conditioning procedures. The aim was to determine how the different measures are differently sensitive to EC effects. Although self-report indicated conditioning effects already after 1 conditioning procedure and in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
0
14
0
4
Order By: Relevance
“…For instance, evaluative conditioning has long been used to change products (e.g. IT devices) affectively in order to make them more appealing, but whether the effects of evaluative conditioning are better assessed with subjective or objective measures remains unanswered (Walla, Koller, Brenner, & Bosshard, 2017).…”
Section: Emotion Researchmentioning
confidence: 99%
“…For instance, evaluative conditioning has long been used to change products (e.g. IT devices) affectively in order to make them more appealing, but whether the effects of evaluative conditioning are better assessed with subjective or objective measures remains unanswered (Walla, Koller, Brenner, & Bosshard, 2017).…”
Section: Emotion Researchmentioning
confidence: 99%
“…However, the SRM demonstrated clear between group differences. Another recent study by Walla, Koller, Brenner and Bosshard [26] used varying rounds of evaluative conditioning of liked and disliked brands and found that conditioning effects resulted in selective differences in self-report versus SRM measures. These findings further support the notion that objectively accessible processes play a pivotal role in our behaviour regardless of conscious awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Preferences related to urban neighbourhoods were reported to be subject to discrepancies between conscious and non-conscious information processing [4]. Brand attitude can change non-consciously without affecting conscious processing [5][6][7] and emotion pictures are processed differently depending on conscious or non-conscious measures being taken [8,9]. SRM became a highly appreciated tool to quantify raw affective responses in the absence of any awareness and it got introduced to various different disciplines including clinical and industrial areas, even marketing [10][11][12][13][14][15].…”
mentioning
confidence: 99%